2020
DOI: 10.1002/jrsm.1399
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in framework synthesis as a systematic review method

Abstract: Double-spacing not needed AMA Referencing Reviews offer a general overview of a particular field or topic, providing the reader with an appreciation of the importance of the work, a summary of recent developments, and a starting point in the specialist literature. Reviews are not limited as to the number of pages, tables, figures and references that may be included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
120
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 94 publications
(673 reference statements)
0
120
0
Order By: Relevance
“…Where studies referred to outcomes that were related to neonatal care, textual data were analyzed by two researchers to derive common themes and new outcome domains developed, using framework synthesis methods. 17,28 The research team approached the study design and analysis using a scientific realist critical perspective. 29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where studies referred to outcomes that were related to neonatal care, textual data were analyzed by two researchers to derive common themes and new outcome domains developed, using framework synthesis methods. 17,28 The research team approached the study design and analysis using a scientific realist critical perspective. 29…”
Section: Discussionmentioning
confidence: 99%
“…Framework synthesis is suitable for mixed methods research synthesis that deals with complex concepts, because it can fractionate and manage heterogenous data to generate, explore, and/or test theory. The extent of the development of theory depends on the contextual, theoretical, and process characteristics and on review team challenges (Brunton et al). Examples of framework synthesis utilized to scope or map research for policy and research development are increasingly evident .…”
Section: Discussionmentioning
confidence: 99%
“…This review adopted a framework synthesis approach, enabling a structured approach to both organizing and interpreting data. (15) Prior to conducting the review, the research team developed a protocol to guide the review, outlining details of the inclusion criteria and databases to search. The review is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…A framework synthesis(15) approach was adopted, incorporating five stages of familiarisation, framework selection, indexing, charting and mapping and interpretation. An initial framework reflecting key components relating to a person’s access and interaction with bereavement care across the three levels of the NBA tiers was developed using two sources: literature on known inequities in provision of palliative care (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of this framework analysis is to assess the number and scope of self-reported symptom tracker programs focused on the United States and COVID-19. An innovative best fit framework analysis was chosen because of its strength, utility, and appropriateness in drawing conclusions for an evolving subject [ 15 , 16 ]. According to Booth and Carroll [ 17 ], the best fit framework approach is considered a highly structured and pragmatic methodology for research synthesis suited for qualitative research with specific questions, a limited time frame, and issues that have been previously identified; this served the purpose of our research well [ 18 ].…”
Section: Introductionmentioning
confidence: 99%